The Relationship Between Functional Parameters Derived from Diffusion-Weighted MRI and 18F-Fluorodeoxyglucose PET/CT in Head and Neck Squamous Cell Carcinoma: A Systematic Review and Meta-analysis - Garau, Ludovico Maria; Rensi, Marco; Bastianutti, Livio; Bologna, Roberto; Povolato, Michele; Capobianco, Decio; Gregorio, Fernando Di (International Archives of Otorhinolaryngology, 2025)
Over the past decade, a mechanistic hypothesis emerged linking limited water diffusivity (often reflecting densely packed, actively dividing tumor cells) to elevated glucose uptake in head and neck cancer.A systematic search of MEDLINE via PubMed identified eligible studies assessing the correlation between apparent diffusion coefficients from diffusion-weighted MRI and standardized uptake values from 18F-fluorodeoxyglucose PET/CT in head and neck cancer. Weighted correlation coefficients (ρ) were computed using Fisher Z transformations, and 95% confidence intervals (CIs) were calculated. Heterogeneity was evaluated with Higgins's inconsistency index, and potential publication bias was evaluated by visually inspecting funnel plots.A total of 25 articles, encompassing 790 patients, were systematically appraised to summarize the available evidence regarding the relationship between functional parameters in head and neck cancer. Thirteen studies, involving 367 patients and reporting a statistically significant inverse correlation between functional parameters, were summarized in the forest plot; the pooled correlation coefficient estimate was ρ = −0.55 (95% CI: −0.624 to −0.473; P < 0.05), with low heterogeneity. A further 12 studies were systematically reviewed for qualitative analysis due to the absence of significant relationships.The correlations observed in some studies between apparent diffusion coefficients and standardized uptake values may provide insights to develop metrics for evaluating treatment efficacy and predicting clinical outcomes in head and neck cancer. However, not all studies confirmed this result, possibly due to factors such as molecular characteristics or clinical settings.
Keywords: head and neck squamous cell carcinoma; diffusion-weighted magnetic resonance imaging; positron emission tomography and computed tomography; apparent diffusion coefficient